PRODUCTION TECHNOLOGY, QUALITY CONTROL AND SAFETY OF CUSTARD HONEY CAKES - E. V. Boyarshinova (Современная наука и инновации)
Modern gingerbread production technologies are diverse and include the use of unconventional raw materials and additives. However, these technologies do not contribute to maintaining high quality and safety ofproducts over a long period of storage. In this regard, quality and safety control of custard cakes was carried out with the use of low-temperature cooling of the welding and its long-term storage. The product included wheat flour, natural honey, granulated sugar, margarine, baking soda, chicken eggs, chocolate and water. The production technology included the preparation of syrup, brewing, its subsequent exposure for 7 days, kneading dough, forming gingerbread and drying them. The resulting gingerbread sample was subjected to laboratory tests on quality indicators for compliance with the requirements of GOST 15810-2014 and on safety indicators for compliance with the requirements of the Technical Regulations of the Customs Union (TR CU) 021/2011 "On food safety". It was found that the product fully complies with the requirements of GOST 15810-2014for organoleptic and physico-chemical parameters and the re-quirements of TR CU 021/2011 "On food safety" for the content of residual amounts of pesticides, mycotoxins, toxic elements and microbiological safety indicators.